A Metal‐Like Conductive Elastomer with a Hierarchical Wrinkled Structure. Issue 7 (12th December 2019) - Lee, Seokmin; Song, Yongkwon; Ko, Yongmin; Ko, Younji; Ko, Jongkuk; Kwon, Cheong Hoon; Huh, June; Kim, Sang‐Woo; Yeom, Bongjun; Cho, Jinhan
Abstract: For the development of wearable electronics, the replacement of rigid, metallic components with fully elastomeric materials is crucial. However, current elastomeric electrodes suffer from low electrical conductivity and poor electrical stability. Herein, a metal‐like conductive elastomer with exceptional electrical performance and stability is presented, which is used to fabricate fully elastomeric electronics. The key feature of this material is its wrinkled structure, which is induced by in situ cooperation of solvent swelling and densely packed nanoparticle assembly. Specifically, layer‐by‐layer assembly of metal nanoparticles and small‐molecule linkers on elastomers generates the hierarchical wrinkled elastomer. The elastomer demonstrates remarkable electrical conductivity (170 000 and 11 000 S cm −1 at 0% and 100% strain, respectively), outperforming previously reported elastomeric electrodes based on nanomaterials. Furthermore, a fully elastomeric triboelectric nanogenerator based on wrinkled elastomeric electrode exhibits excellent electric power generation performance due to the compressible, large contact area of the wrinkled surface during periodic contact and separation. Abstract : Highly conductive and wrinkled elastomers are realized by in situ cooperation of solvent swelling and densely packed nanoparticle assembly. The elastomers exhibit electrical conductivity of 170 000 and 11 000 S cm −1 at 0% and 100% strain, respectively. Furthermore, elastomeric electrode‐based triboelectric nanogenerators show excellent electric outputs by the wrinkled structure and compressible properties of the contact electrode.